2010
DOI: 10.1002/da.20610
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy of interpersonal therapy-group format adapted to post-traumatic stress disorder: an open-label add-on trial

Abstract: IPT-G PTSD was effective not only in decreasing symptoms of PTSD, but also in decreasing symptoms of anxiety and depression. It led to significant improvements in social adjustment and quality of life. It was well tolerated and there were few dropouts. Our results are very preliminary; they need further confirmation through randomized controlled clinical trials.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
25
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(27 citation statements)
references
References 21 publications
2
25
0
Order By: Relevance
“…That adaptation was continued into the current study. Others (e.g., Campanini et al, 2010; Krupnick et al, 2008; Talbot et al, 2011) have adapted IPT for populations of women with interpersonal trauma in a similar way. Efforts to improve social support were aimed at supports outside and inside the prison.…”
Section: Methodsmentioning
confidence: 99%
“…That adaptation was continued into the current study. Others (e.g., Campanini et al, 2010; Krupnick et al, 2008; Talbot et al, 2011) have adapted IPT for populations of women with interpersonal trauma in a similar way. Efforts to improve social support were aimed at supports outside and inside the prison.…”
Section: Methodsmentioning
confidence: 99%
“…Although psychotherapies such as exposure therapy and cognitive processing therapy are first line treatments for trauma-related disorders in Europe and North America, and have been used successfully in LMICs [7], our mental health care needs assessment in this disaster-affected Sichuan population indicated that PTSD symptoms were one component of broader emotional distress and pervasive disruption of relationships. Drawing on prior studies showing the efficacy of IPT in LMICs and with trauma-affected populations [8-11], we theorized that the relational focus of Interpersonal Psychotherapy (IPT) would be well-aligned with local needs. IPT delivered by area personnel was selected in order to contribute to capacity building.…”
Section: Background and Rationalementioning
confidence: 99%
“…Initial evidence suggests that IPT may also benefit patients with posttraumatic stress disorder ([PTSD]; Bleiberg & Markowitz, 2005; Campanini et al, 2010; Krupnick et al, 2008; Ray et al, 2010; Robertson et al, 2004; Robertson et al, 2007). There are at least two rationales for testing IPT for this population.…”
Section: Introductionmentioning
confidence: 99%